Linguistic Patterns of Students in Academic Short Message Communication with Lecturers - Alexi Sapta Pratama (Journal of Education, Linguistics, Literature and Language Teaching, 2026)
The use of digital communication media has increasingly shaped the way students interact with lecturers, especially through short messaging applications. This study aims to provide a clear and systematic description of the linguistic patterns used by students in academic communication with lecturers via short messages. Using a descriptive qualitative approach, this research applies content analysis to a set of students’ short messages. The findings show that students’ language use reflects variations in formality, the use of greetings, lexical choice, and sentence structure. These results indicate that students’ awareness of academic context influences how messages are written. This study is expected to serve as an accessible reference for understanding academic communication through digital messaging, particularly for beginner researchers